Photo-curable highly water-repellent nanocomposite coatings - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (WILEY-BLACKWELL, 2013)
Modification and use of natural products have gained a lot of interest in recent years due to their environmental friendliness and their availability from different sources. In this study, (castor oil)-based photo-curable highly hydrophobic coatings were prepared and characterized. Castor oil was first modified with 3-isocyanatopropyltriethoxysilane and then hydrolyzed prior to the coating preparation. The resulting precursor was mixed with norbornyl acrylate and hexanediol diacrylate, and highly roughened hydrophobic coatings were prepared with the aid of fluorinated/nonfluorinated alkoxysilane coupling agents and hydrophobic fumed nanosilica particles. The coatings were applied on borofloat glass. The addition of fluorine and nanosilica showed a significant impact on the properties of the coatings. As the fluorine and nanosilica contents were increased in the formulations, flame retardancy and the contact angle values of the coatings increased. The surface roughness of the coatings increased with the addition of hydrophobic fumed nanosilica particles. Also, the relation between the surface energy and the contact angle values of the coatings was investigated. J. VINYL ADDIT. TECHNOL., 19:3138, 2013. (c) 2013 Society of Plastics Engineers
Keywords: OIL-BASED POLYURETHANES; SOL-GEL PROCESS; CASTOR-OIL; SUPERHYDROPHOBIC SURFACES; RENEWABLE RESOURCE; POLYOL; GLASS